PROTOTIPE SISTEM PENDUKUNG KEPUTUSAN PENDETEKSIAN KONDISI BAYI DENGAN FUZZY TSUKAMOTO - Agung Setiawan; Budi Yanto; Kiki Yasdomi (RJOCS (Riau Journal of Computer Science), 2018)
Baby condition is a condition that is vulnerable to environmental changes, especially weather changes. Knowledge of a mother in maintaining baby health should also be considered, especially in terms of nutritional intake. A healthy baby's condition affects the baby's growth and development. The creation of a decision support system should be preceded by collecting and analyzing data according to need. In this study using baby feeding variables, namely Body Temperature (37.70c), Fuss (2.4), Restless (4.5), BABSering (3.7), BABEncer (5.6), Bloating (3.5), Nausea (3.7), Vomiting (3.2 ), Stomach Pain (2.7) and Itchy Skin (2.8). The results of the calculations will result in defoliation as follows: Measles (1.48), Septis (1.48), Diarrhea (1.48), ISPA (7.36), Enteritis (0.77), Miliaria (1.48), OMP (1.48) and Varicela (1.48). The range of fuzzy values ranges from 0 to 1, so the results obtained that the baby has enteritis or stomach problems. The calculation of defuzification obtained result of 8.1, so the condition of the baby is very sick and should be handled immediately by bringing to the medical personnel